2003
DOI: 10.1002/app.12170
|View full text |Cite
|
Sign up to set email alerts
|

Microcellular foam of polymer blends of HDPE/PP and their composites with wood fiber

Abstract: ABSTRACT:In this study, the effects of batch processing conditions (foaming time and temperature) and blend composition as well as the effect of incorporating wood fiber into the blends on the crystallinity, sorption behavior of CO 2 , void fraction, and cellular morphology of microcellular foamed high-density polyethylene (HDPE)/polypropylene (PP) blends and their composites with wood fiber were studied. Blending decreased the crystallinity of HDPE and PP and facilitated microcellular foam production in blend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
146
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(163 citation statements)
references
References 16 publications
10
146
0
Order By: Relevance
“…Dilution of one polymer with a small amount of the other has been found to be preferable relative to near-equal-mass mixtures. Rachtanapun et al [187] have found that blending HDPE and PP leads to reduced crystallinity, which facilitates CO 2 foaming, whereas the addition of wood fiber to the same blend inhibits foaming because of reduced CO 2 solubility and increased CO 2 escape rate. However, in some systems, crystalline structures can assist foaming.…”
Section: Cells CM à3mentioning
confidence: 98%
“…Dilution of one polymer with a small amount of the other has been found to be preferable relative to near-equal-mass mixtures. Rachtanapun et al [187] have found that blending HDPE and PP leads to reduced crystallinity, which facilitates CO 2 foaming, whereas the addition of wood fiber to the same blend inhibits foaming because of reduced CO 2 solubility and increased CO 2 escape rate. However, in some systems, crystalline structures can assist foaming.…”
Section: Cells CM à3mentioning
confidence: 98%
“…It was shown by Pilla et al [2] that the simultaneous addition of talc and CE leads to increased cell density and more uniform cell structure. Fillers, such as wood particles [8] or clay nanoparticles [9] are also known to act as crystal nucleating agents and change the melt viscosity. Moreover fillers influence the microstructure and thus the mechanical and thermal properties of the foams [10].…”
Section: Introductionmentioning
confidence: 99%
“…[3,5,13,15]. As is the case with physical blowing agents, chemical blowing agents produce gas that is dissolved in the polymer [9,12]. The gas release reaction can be endothermic or exothermic [7,9,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…As is the case with physical blowing agents, chemical blowing agents produce gas that is dissolved in the polymer [9,12]. The gas release reaction can be endothermic or exothermic [7,9,15,18]. When using chemical blowing agents, one should take into account the fact that their decomposition temperature must be exceeded in order to produce the required amount of gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation